THE RELATIONSHIPS AMONG JOB SATISFACTION, EMOTIONAL EXHAUSTION, CYNICISM, JOB ENGAGEMENT AND CREATIVE WORK INVOLVEMENT, STUDY ON EDUCATION INSTITUTIONS IN INDONESIA - Kusumawati, Heni; Prajogo, Wisnu; Wijaya, Nikodemus Hans Setiadi (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the relationship between job satisfaction, cynicism, emotional exhaustion, job engagement and creative work involvement. This study used 200 respondents who came from educative and non-educative workers in Indonesia. The research data have fulfilled the validity, reliability and normality tests. Hypothesis testing uses the Structural Equation Model (SEM) with Confirmatory Analysis. The results showed that job satisfaction positively influences on work engagement at α = 1%, while emotional exhaustion has no influence on the direction of the negative relationship to job engagement. The cynicism variable has no significant influence on job engagement with the direction of a positive relationship. While the variable job engagement positively influences creative work involvement at α = 1%.